The Ebbinghaus illusion revisited: Behavioral shift in task-solving between 4-year-olds, 6-year-olds, and adolescents - Schulze, Cornelia; Buttelmann, David (Cognitive development, 2025)
Visual context influences humans’ interpretation of stimuli. The Ebbinghaus illusion demonstrates how physical context cues can lead to distorted perceptions. Prior studies on young children’s context-sensitivity leave it open whether older age groups are indeed more susceptible to visual illusions than younger ones or whether young children use different mechanisms when solving this task. This study addresses these questions by investigating 4-year-olds’ (n = 41), 6-year-olds’ (n = 46), and adolescents’ (n = 66) performance in an Ebbinghaus illusion task. We especially focused on 4-year-olds’ performance, including a novel control condition, to help disentangle the non-expected findings from previous studies. The results replicated previous findings of a developmental increase in context-sensitivity in the Ebbinghaus task. However, there was a behavioral shift in task-solving between 4- and 6-year-olds. While younger children appeared to rely on a heuristic, evaluating the whole area covered by the target and the context cues, 6-year-olds and adolescents were influenced by the illusion. These findings suggest that novel paradigms are needed to test 4-year-olds’ sensitivity to physical context cues. •We investigated if young children are susceptible to the illusion or use a heuristic.•Results showed increased context-sensitivity (illusion susceptibility) with age.•A behavioral shift in task-solving was observed between 4- and 6-year-olds.•Four-year-olds used a heuristic based on the overall area of target and context circles.